2003
DOI: 10.1590/s1516-31802003000600005
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated head and neck tumors: the contribution of immunohistochemical technique to differential diagnosis

Abstract: Our results demonstrate the fundamental role of the immunohistochemical technique for conclusive diagnosis of undifferentiated tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
1
11
1
Order By: Relevance
“…Similar observations regarding the head and neck region malignancy is predominant in male subjects also observed by Mandalet al 12 In our study it was observed that over one-third patients had cervical lymphadenopathy, one-third had neck mass and one-tenth had mass in nasal/sinonasal region. Almost similar findings was reported Bianchini et al 13 who obtained the lymph nodes (20.9%), pharynx and neck mass (16.3%), paranasal sinus (14.0%) and nose (11.6%) constituted the majority of sites.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar observations regarding the head and neck region malignancy is predominant in male subjects also observed by Mandalet al 12 In our study it was observed that over one-third patients had cervical lymphadenopathy, one-third had neck mass and one-tenth had mass in nasal/sinonasal region. Almost similar findings was reported Bianchini et al 13 who obtained the lymph nodes (20.9%), pharynx and neck mass (16.3%), paranasal sinus (14.0%) and nose (11.6%) constituted the majority of sites.…”
Section: Discussionsupporting
confidence: 88%
“…It was not possible in 2 patients (5.7%) of cases. Bianchini et al 13 reported 18.6% and Gatter et al 5 reported 6.7% inconclusive results. This could be due to technique differences, different antigen retrieval methods or the unavailability of the antigen suspected.…”
mentioning
confidence: 96%
“…This proportion is higher than the 27.9% confirmation rate of carcinomas in a study by Bianchini et al in Italy [9]. Lesions that were confused with carcinomas included 8 (12.9%) sarcomas, 8 (12.9%) lymphomas, 6 (9.7%) neuroendocrine tumors and 1 carcinosarcoma.…”
Section: Discussionmentioning
confidence: 61%
“…In this regard, Bhagat et al could categorize 98.65%, Vege DS et al could categorize 85.5%, 7 Coindre JM et al (1986) could categorize 90%, while Michie et al (1987) could arrive at a diagnosis in 86% of undifferentiated tumours, by immunohistochemistry. In the study by Bianchini et al, immunohistochemistry allowed a conclusive diagnosis for 60.5% of tumours, 8 and was suggestive for 20.9%.…”
Section: Discussionmentioning
confidence: 94%
“…There were 7 cases of small cell (14%), 1 case of spindle cell (2%) and no case of pleomorphic (0%) category. Bianchini et al (2003) divided the undifferentiated tumours morphologically into round cell, epithelioid cell, spindle cells, myxoid pattern and pleomorphic, and found that round cell was the most prevalent pattern (51.2%). There were other authors who did not categorize the tumours morphologically and applied a complete panel of antibodies to all tumours.…”
Section: Diagnosis On Immunohistochemistrymentioning
confidence: 99%